Dengue Immunopathology and Control Strategies - Aparecida Sperança, Márcia (IntechOpen, 2017)
This edited book Dengue - Immunopathology and Control Strategies contains eight chapters divided in three sections that underline important aspects of dengue virus, the most prevalent and life-threatening arbovirus in the world, including virus replication cycle and pathology, diagnostic methods, and control. The first section brings knowledge on basic aspects of dengue virus replication which can be associated to its immunopathology. The second section includes two chapters on dengue diagnosis and emphasizes that in spite of the many scientific efforts, this subject continues to be a drawback in the disease control. Vector-based control strategies are discussed in the third section which also contains a chapter on regulation of dengue vaccines and the experience of Mexico in the implementation of the unique registered dengue vaccine.